Surfactant for petroleum demulsification, structure, classification, and properties. A review - Saad, M. A.; Nour, A. H.; R. M., Yunus; H. S., Ali (IOP Publishing, 2020)
Crude oil as a complex fluid often consists of colloidal particles. These colloidal particles are made up of asphaltenes and resins diffused in a blend of aliphatic and aromatic solvents. At various stages of crude oil production, there is usually an occurrence a water-in-oil emulsion. The stability of the emulsion formed is dependent on the occurrence of the interfacial barrier which prevents the coalescence of the dispersed water droplets. Several operational difficulties are often encountered during crude oil processing as a result of the presence of water. These difficulties range from corrosion in equipment and pipelines as well as an increase in the production cost. Hence, to mitigate these economic and operational challenges, it is crucial to ensure that the water is separated from the crude oil prior to transporting or refining the oil. Demulsification using surfactant is one of the effective techniques used for the separation of crude oil from water. This paper presents a short review of the various application of surfactants for demulsification, their structure, classification as well as their properties. In addition, the mechanism and techniques for demulsification of crude oil were also presented.